2019
DOI: 10.1016/j.apcata.2019.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the hydrogenation of pure and crude HMF to furan diols using Ru/C as catalyst

Abstract: 5-hydroxymethylfurfural (HMF) is one of the most important renewable platform-chemicals, a very valuable precursor for the synthesis of bio-fuels and bio-products. In this work, the hydrogenation of HMF to two furan diols, 2,5-bis(hydroxymethyl)furan (BHMF) and 2,5-bis(hydroxymethyl)tetrahydrofuran (BHMTHF), both promising renewable monomers, was investigated. Three commercial catalysts, Ru/C, Pd/C and Pt/C, were tested in the hydrogenation of aqueous HMF solutions (2-3 wt%), using a metal loading of 1 wt% res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
75
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(80 citation statements)
references
References 71 publications
5
75
0
Order By: Relevance
“…The enzymatic hydrolysis of raw Arundo donax L. and the CRR recovered by the hydrolysis of Arundo donax L., previously separated from the embedded Amberlyst-70 by sieving, was conducted at pH = 4.8 and 50 • C in a 150 mL flask employing 50 mL of the 0.05 M citrate buffer solution and the enzyme Cellic ® CTec2, shaking at 160 rpm. Different substrate loadings and dosages of enzymes were investigated in the present study, in agreement with the ranges reported in the literature [32,79,81]. Every 24 h, samples of 2 mL were withdrawn, cooled in ice in order to stop the enzymatic activities, centrifuged and analysed by HPLC for determining the glucose concentration.…”
Section: Enzymatic Hydrolysis Of Arundo Donax Lsupporting
confidence: 66%
See 2 more Smart Citations
“…The enzymatic hydrolysis of raw Arundo donax L. and the CRR recovered by the hydrolysis of Arundo donax L., previously separated from the embedded Amberlyst-70 by sieving, was conducted at pH = 4.8 and 50 • C in a 150 mL flask employing 50 mL of the 0.05 M citrate buffer solution and the enzyme Cellic ® CTec2, shaking at 160 rpm. Different substrate loadings and dosages of enzymes were investigated in the present study, in agreement with the ranges reported in the literature [32,79,81]. Every 24 h, samples of 2 mL were withdrawn, cooled in ice in order to stop the enzymatic activities, centrifuged and analysed by HPLC for determining the glucose concentration.…”
Section: Enzymatic Hydrolysis Of Arundo Donax Lsupporting
confidence: 66%
“…Humins could be present on the CRR and Amberlyst-70 surfaces, contributing to hamper the conversion of cellulose into glucose. To partially remove humins, the whole solid recovered from run 13 was washed with acetone, which is efficient for this purpose [57,81], and subsequently dried under vacuum at 50 • C and reprocessed. The reaction was carried out with the CRR loading of 17 wt%, analogously to the conditions of the first step.…”
Section: Chemical Hydrolysis Of Cellulose-rich Residue (Crr) To Glucosementioning
confidence: 99%
See 1 more Smart Citation
“…The molecule 5‐hydroxymethylfurfural (HMF) possesses a hydroxyl group and an aldehyde group at the 2,5 positions of the furan ring, which enable it to perform different types of reactions, such as hydrogenation, [2,3] oxidation, [4,5] rearrangement, [6] decomposition [7] and polymerization [8] . HMF can be converted to value‐added fine chemicals and liquid fuels, such as levulinic acid, [7] 2,5‐furandialdehyde (DFF), [9,10] 2,5‐furandicarboxylic acid (FDCA) [11,12] .…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the research on the biochemical synthesis of DHMF is meaningful to mechanism research, drugs development and clinical application. In fact, selective hydrogenation of 5-HMF and selective of catalysts are the key on the chemical synthesis of DHMF (Fulignati et al 2019). Meanwhile, there are also studies showing that this transformation can be accomplished through biotransformation (He et al 2018;Li et al 2017).…”
Section: Introductionmentioning
confidence: 99%